Infertility related stress and marital life in Iranian infertile women who referred to Isfahan infertility treatment clinic - M Mollaiy nezhad; M Jaaferpour; Sh Jahanfar; R Jamshidi (JRI, 2001)
The literature is full of anecdotal evidence about linkage between infertility and stress and deleterious impacts that infertility stress can have on the functioning of a marriage and the couple’s life quality. This study was designed to determine the corrilation between infertility related stress and marital adjusment in women who reffered to Isfahan and infertility treatment clinic A Corrolational-one group research design was used to measure infertility related stress and marital adjusment of infertile women using data from a questionnaire including [socio-demographic data, infertility related stress and Dyadic adjusment scale (DAS)] and investigation of relationship of these two variables from different aspects. All of the participants had experienced infertility stress (in different degrees) and about half of them (46%) were maritally distressed . for these women, infertility stress scores were significantly related to economical problems, family composition, duration of treatment and confidence one will have a child for marital adjusment, duration of infertility and a positive history of failed pregnancy were only variables that were significantly related to this variable. For these women infertility stress scores singnificantly related to deterioration of marital adjusment.(r=-0.39, P<0.001) As hypothesized, infertility related stress, had deleterious impact on the marital life of infertile women. Meaningful characteristics were identified that could guide clinicians to those women at risk for increasing stress and marital distress. These variables are as follows: a low socioeconomic status, and unsuccessful treatment outcome, failed treatment cycles, family composition and duration of infertility and it’s treatment.
Keywords: Stress, Infertility, Marital adjustment